2022
DOI: 10.3346/jkms.2022.37.e141
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Clinical Characteristics of Kawasaki Disease After Coronavirus Disease (COVID-19) Pandemic: A Database Analysis

Abstract: Background The impact of the coronavirus disease 2019 (COVID-19) pandemic on Kawasaki disease (KD) has not yet been established. We investigated changes in the observed number and severity of KD cases and accompanying coronary artery complications during the COVID-19 pandemic in Korea. Methods This retrospective observational study included patients aged < 18 years with acute-phase KD diagnosed between March 2018 and February 2021. Data were extracted from the Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Specifically, we observed that the incidence rate in children aged <1 year was high compared with that in the other age groups, with a significant increase from the values in the previous years. This result is consistent with those of previous studies conducted in the United States and Japan and domestic multicenter studies ( 11 , 25 ). As expected, the social behavior of children under 1 year of age is unlikely to have changed significantly between the pre-pandemic and pandemic periods.…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, we observed that the incidence rate in children aged <1 year was high compared with that in the other age groups, with a significant increase from the values in the previous years. This result is consistent with those of previous studies conducted in the United States and Japan and domestic multicenter studies ( 11 , 25 ). As expected, the social behavior of children under 1 year of age is unlikely to have changed significantly between the pre-pandemic and pandemic periods.…”
Section: Discussionsupporting
confidence: 94%
“…As reported by Kim et al [29], even though there was an increase in the proportion of infants under 1 year of age hospitalized for KD, the prevalence of refractory KD and challenging cases did not significantly increase during social distancing. While MIS-C and KD exhibit marked inflammation and inflammatory vasculopathy, further research is essential to ascertain whether these conditions represent distinct immunopathogenic disorders [30].…”
Section: Discussionsupporting
confidence: 55%
“… 53 , 78 It is possible that some of the decrease in KD may be related to misclassification of KD patients as having MIS-C, although this is more likely related to decrease exposure to possible infectious/environmental triggers. 79 , 80 A case series from Korea, where the incidence of MIS-C during the pandemic has been very low, compared 19 KD patients with a history of prior COVID-19 with 26 KD patients without, and noted few differences, although patients with prior COVID were older with more severe disease, which may suggest some similiarities with MIS-C. 81 The association of prior COVID-19 and vaccination with the risk of subsequent KD is largely unknown. In contrast, a report from Seattle noted that patients with a prior history of KD did not have adverse outcomes when either infected with SARS-CoV-2 or vaccinated with mRNA COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%